Relationship between initial B-type natriuretic peptide levels and detection of atrial fibrillation with an insertable cardiac monitor in cryptogenic stroke: CRYPTON-ICM registry - Moriyama, Takuya; Todo, Kenichi; Yamagami, Hiroshi; Kimura, Yoko; Yamamoto, Shiro; Nagano, Keiko; Doijiri, Ryosuke; Yamazaki, Hidekazu; Sonoda, Kazutaka; Koge, Junpei; Nakayama, Taira; Iwata, Tomonori; et al. (Frontiers in Neurology, 2024)
High B-type natriuretic peptide (BNP) levels are associated with new atrial fibrillation (AF). This study investigated the distribution of AF detection rates according to BNP levels in patients with cryptogenic stroke (CS) using an insertable cardiac monitor (ICM). We enrolled consecutive patients with CS who underwent ICM implantation between October 2016 and September 2020 at eight stroke centers in Japan. Those with BNP levels were divided into three groups by tertiles. We evaluated the association of BNP levels with AF detection. Youden's index was calculated to identify the optimal cutoff for BNP. Of 417 patients, we analyzed 266 patients with BNP data. The tertile range of BNP level was 19.0 to 48.5 pg/mL. AF detection rate was 13.3 %/year, 12.8 %/year, and 53.7 %/year in the low-BNP (≤ 19.0), mid-BNP (19.1-48.4), and high-BNP (≥ 48.5) groups, respectively (log-rank trend P < 0.01). Compared with low-BNP group, the adjusted hazard ratios for AF detection in mid-and high-BNP groups were 0.91 (95% confidence interval [CI] 0.46-1.78) and 2.17 (95% CI 1.14-4.13), respectively.Receiver operating characteristic curve analysis showed the optimal cutoff value was 43.4 pg/mL. The area under curve using BNP to predict AF detection was 0.69. The BNP level was associated with AF detection in patients with CS. This relationship changed around the BNP levels of 40-50 pg/mL.